2012
DOI: 10.4048/jbc.2012.15.2.211
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Ultrasound and Ultrasound-Guided Fine Needle Aspiration Cytology in Preoperative Assessment of Axillary Lymph Node Metastases in Breast Cancer

Abstract: PurposeWe performed this study to detect preoperative axillary metastases with ultrasound (US)-guided fine needle aspiration biopsy (FNAB), to eliminate the need for time-consuming and costly sentinel lymph node (SLN) scintigraphy and biopsy steps in the treatment of breast cancer patients, and in that of with suspicious US findings, and to evaluate the accuracy of preoperative US-guided FNAB for patients with suspicious lymph node metastases on US.MethodsPatients with a suspicious breast lump or histopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 28 publications
2
35
0
2
Order By: Relevance
“…The majority (70–90%) underwent axillary dissection unnecessarily. This led to scalene lymph node biopsy becoming a commonly accepted method [17]. The common use of mammography screening has led to the early diagnosis of small-sized BCs.…”
Section: Discussionmentioning
confidence: 99%
“…The majority (70–90%) underwent axillary dissection unnecessarily. This led to scalene lymph node biopsy becoming a commonly accepted method [17]. The common use of mammography screening has led to the early diagnosis of small-sized BCs.…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of ultrasonographically (US)-guided methods for nonpalpable lesions, FNAC and CNB have been used more widely in the evaluation of nonpalpable breast lesions (Oz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, thickness of the lymph node cortex is most highly associated with the presence of metastasis and may contribute to US-guided FNA (5). Oz et al (5) revealed that a cortical thickness >4.0 mm had a sensitivity of 86% and specificity of 87%, whereas at the cut-off point of 3.0 mm, specificity decreased to 37%. However, results in the literature are heterogenous, as ultrasonographic examination is operator-dependent and machine-dependent and there is a great variation in sensitivity and specificity when only US is used for evaluation of axillary lymph nodes (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…(20)(21)(22)(23)(24)(25)(26)(27)(28). US-guided FNA has a high accuracy rate (5,7). Therefore, controversy concerning US-guided FNA cytology of axillary lymph nodes vs. SNB in early-stage breast cancer, in addition to the paucity of comparative studies between the two methods in Brazilian women, informed the current study design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation